The BP oil spill - Benoit, Peter, 1955- (New York : Children's Press, 2011)
Photographs, maps, time lines, and easy-to-follow text describe the events surrounding the 2010 British Petroleum oil spill in the Gulf of Mexico.
Trouble in the gulf : what happened to the Deepwater Horizon? -- Deep water disaster : what problems did the rig have before the explosion? -- From bad to worse : what caused the oil slick to spread? -- Cleanup : what was done to clean up the oil spill? -- After the spill : will the oil be with us forever? -- True statistics -- Important words.
Includes bibliographical references (p. 44) and index.
b
b
Keywords: BP (Firm) -- Juvenile literature; BP (Firm).; BP Deepwater Horizon Explosion and Oil Spill, 2010 -- Juvenile literature; Oil spills -- Mexico, Gulf of -- History -- 21st century -- Juvenile literature; Oil spills -- Environmental aspects -- Mexico, Gulf of -- History -- 21st century -- Juvenile literature; Oil wells -- Mexico, Gulf of -- Blowouts -- History -- 21st century -- Juvenile literature; BP Deepwater Horizon Explosion and Oil Spill, 2010.; Oil spills -- Mexico, Gulf of -- History -- 21st century; Oil spills -- Environmental aspects -- Mexico, Gulf of -- History -- 21st century; Oil wells -- Mexico, Gulf of -- Blowouts -- History -- 21st century